Biodiversity of Lactuca aculeata germplasm assessed by SSR and AFLP markers, and resistance variation to Bremia lactucae. (August 2015) - Jemelková, Michaela; Kitner, Miloslav; Křístková, Eva; Beharav, Alex; Lebeda, Aleš
Abstract: In total, seventy two Lactuca aculeata and three Lactuca serriola samples originating from natural populations of these species in Turkey, Jordan, and Israel were analysed by eight microsatellite and 287 amplified fragment length polymorphism (AFLP) markers. Neighbor–Network and Bayesian clustering were used for visualisation of the differences among the analysed L. aculeata and L. serriola samples, and to confirm hybrid origin ( L. aculeata × L. serriola ) of three samples (343-8A, 343-8B, 54/07) previously indicated by their morphological traits. Molecular data reflect the geographical origin, i.e., the clustering of samples according to their country of origin. Samples from neighbouring parts of Jordan and Israel expressed similar genetic characteristics, indicating the possibility of migration or artificial introduction of plant material. Forty-one L. aculeata samples were screened for their response to five Bremia lactucae races (Bl: 17, Bl: 18, Bl: 24, Bl: 27, and Bl: 28). Susceptible reactions of L. aculeata prevailed. L. aculeata samples were most frequently susceptible to races Bl: 18, Bl: 24, Bl: 27, Bl: 28; and least susceptible to Bl: 17. No highly efficient source of resistance was detected; however, race-specific reaction patterns were frequently recorded, indicating the possible presence of some race-specific resistance factors/genes in the studied samples of L. aculeata . Conservation and exploitation of this material in lettuce breeding is discussed. Highlights: Molecular polymorphism of Lactuca aculeata and resistance to Bremia lactucae were studied. Eight microsatellite and 287 AFLP markers were used. Interspecific hybrids of L. aculeata and Lactuca serriola were revealed. Similar genetic background of plant samples from Israel and Jordan was observed. Variability in race-specific reaction of L. aculeata to B. lactucae was recorded.